TRANSFORMASI KEPEMIMPINAN MADRASAH: PENDAMPINGAN PKKM SEBAGAI INSTRUMEN EVALUASI - Nurqadriani, Nurqadriani; Suriyati, Suriyati; Dahlan, Muh. Nur Fithri; Wahyu, Wahyu (Universitas Islam Malang, 2025)
This community service activity was motivated by the low level of understanding and skills among headmasters, teachers, and staff in implementing the Headmaster Performance Assessment (PKKM) at Madrasah Aliyah Bulukunyi. The aim of this activity was to improve the capacity and readiness of partners in understanding and applying PKKM effectively. The implementation method used the Participatory Action Research (PAR) approach with four stages: socialization, education, training, and evaluation. The training was conducted through workshops and both individual and group mentoring over two months. Evaluation was carried out using pre-tests and post-tests, observations, and interviews. The results showed an increase in participants’ understanding from 40% to 85%, and engagement from 50% to 90%. In addition, 90% of participants reported improved skills in preparing PKKM documents and felt more confident in implementation. The main obstacles faced were limited time, varying levels of initial understanding among participants, and a lack of supporting facilities. Nevertheless, the activity successfully raised collective awareness of the importance of PKKM and had a positive impact on improving school management. It is recommended that this program be continued periodically with enhanced learning tools and the involvement of school supervisors.